Divergent modulation of activated protein C pleiotropic functions by antibodies that differ by a single amino acid - Derek S. Sim; Meenal Shukla; Cornell R. Mallari; José A. Fernández; Xiao Xu; Doug Schneider; Maxine Bauzon; Terry W. Hermiston; Laurent O. Mosnier (Blood Advances)
Abstract: Activated protein C (APC) is a pleiotropic plasma protease with diverse functions derived from its anticoagulant, anti-inflammatory, and cytoprotective activities. The selective uncoupling and/or modulation of these APC activities by antibodies may have therapeutic benefit in diseases such as traumatic bleeding, hemophilia, sepsis, and ischemia. TPP-26870 is an antibody that targets a nonactive site of APC for the selective modulation of APC activities. To optimize the potency of TPP-26870, variants with single amino acid mutation in the complementarity-determining regions (CDRs) were screened, and 21 variants with improved affinity constant were identified. Interestingly, the affinity maturation of TPP-26870 did not merely generate a panel of variants with higher potency in functional assays. Functional data demonstrated that the pleiotropic functions of APC were very sensitive to epitope-CDR interactions. Single amino acid mutations within the CDRs of TPP-26870 were sufficient to elicit divergent antagonistic and agonistic effects on the various APC functional activities. These include prolonged in vitro APC plasma half-life, increased inhibition of anticoagulant activity, and agonistic enhancement of histone H3 cleavage, while having less impact on protease-activated receptor 1 cleavage, compared with TPP-26870. This study illustrates that APC is highly sensitive to non–active site targeting that can lead to unpredictable changes in its activity profile of this pleiotropic enzyme. Furthermore, this study demonstrates the ability to modify APC functions to advance the potential development of APC-targeted antibodies as therapeutics for the treatment of diseases including trauma bleeding, hemophilia, ischemia, and sepsis.